Activities in Daily Living: The development of a new client-centred ADL intervention for persons with stroke. (17th February 2022) - Guidetti, Susanne; Eriksson, Gunilla; von Koch, Lena; Johansson, Ulla; Tham, Kerstin
Abstract: Background: An intervention that contains several interacting components can be defined as a complex intervention. This intervention was developed in accordance with the Medical Research Council (MRC) guidance for complex interventions. Aim: To describe the development, theoretical framework, and content of a client-centred activities in daily living intervention (CADL) for people with stroke. Material and methods: Different steps were used; identifying the evidence base, identifying/developing theory and the modelling process and outcomes in the development of the CADL. The remodelling of the process and content of the intervention that emerged are defined. Results: Findings from a series of qualitative studies of people with stroke demonstrated the need to develop an ADL intervention based on the clients' lived experiences. The theoretical framework is based on empirical research, theories about human occupation and client-centredness. The CADL is applying an occupational and phenomenological perspective in order to enable agency in daily activities and participation in everyday life among persons with stroke. Conclusions and significance: The article can be used as an example of how to present the development and theoretical framework of a new complex intervention in occupational therapy.